Flood Analysis at Ramghat, Pokhara, Nepal Using HEC-RAS (Technical Journal, 2019)
Flooding in Ramghat area of Pokhara, Nepal is the major problem that has to be faced every year by the people residing nearby the area. Main goal of this study was to conduct the flood analysis of Seti River in Ramghat. Catchment area of the Ramghat was calculated to be 574.56 sq. km. using ArcGIS where the area above 5000 m elevation was 52 sq. km. and area below 3000 m elevation was 356 sq. km. Precipitation data of two meteorological stations, Pokhara airport and Lumle, were used in this research for the calculation of peak discharge. PCJ method (1996) was used to estimate the peak flood and also compared with the peak flood calculated using Modified Dicken's formula, WECS/DHM method, Rational method and Sharma and Adhikari (2004) method. Peak flood values were found to be 1918 m3/s and 2336 m3/s by PCJ method for return period of 50 years and 100 years respectively. The HEC-RAS modelling was performed for these flooding situations to determine the water surface profile along the eight cross-sections of the Ramghat. Finally, the floodplain map was prepared using the topographic map and the Google Earth Map. It was found that 50 years flood in Ramghat could inundate three cemetery shades situated along the river banks. Most importantly, 100 years’ peak flood was found more vulnerable for residential buildings too. The flood plain maps prepared in this study can be used by government authorities for planning, decision making, early warning system and disaster risk management. Additionally, the rating curve was prepared for the outlet section of Ramghat that can be used to estimate the river discharge during flooding in future.